Analysis of the Influence of Work Loyalty and Organizational Commitment on Employee Performance through Work Discipline as Intervening Variables at PDAM Tirtasari Binjai - Dian Mayna Antika Sari; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2025)
This study aims to find the direct and indirect influence of work loyalty and organizational commitment on employee performance through work discipline. The research was conducted at PDAM Tirtasari Binjai in 2025. The object of this research is all employees of PDAM Tirtasari Binjai which totals 258 employees consisting of 146 employees with the number of samples taken as many as 59 employees determined by the Slovin formula. The sampling technique used is the purposive sampling technique. The type of data used is primary-quantitative data. Data collection was carried out by distributing questionnaires. The research approach uses an associative-quantitative approach with the SEM-PLS (Structural Equation Modeling - Partial Least Squares) analysis technique. The data from the questionnaire distribution was processed with the SmartPLS 3 application. The results of the study show that work loyalty and organizational commitment directly have a positive and significant effect on work discipline. Work loyalty and organizational commitment directly have a non-significant effect on employee performance. Work discipline directly has a positive and significant effect on employee performance. Job loyalty is the variable that most affects work discipline and work discipline is the variable that most affects employee performance. Work loyalty and organizational commitment indirectly through work discipline have a positive and significant effect on employee performance. Work Loyalty (X1) and Organizational Commitment (X2) were able to contribute 82.3% to the formation of the Work Discipline variable (Z). Meanwhile, Work Loyalty (X1), Organizational Commitment (X2), and Work Discipline (Z) were able to contribute 72.3% to the formation of the Employee Performance variable (Y).